The Influence of Price, Product Quality, and Brand on Purchasing Decisions at Thrifting in Pasar Melati, Medan - Angelica Marito Sitanggang; Misa Renata Ginting; Roza Maya Sari; Efry Kurnia (International Forum of Researchers and Lecturers, 2025)
Consumer purchasing decisions for thrifting products are influenced by factors such as price, quality, trends, and availability. Consumers tend to choose thrifting because the prices are more affordable and the products offer uniqueness that is not mass-produced. As the popularity of thrifting increases, competition is also becoming more intense. Business actors are racing to develop marketing strategies through social media and marketplaces. Product differentiation, competitive pricing, and attractive services have become key elements in attracting consumer interest. The population in this study includes all consumers who purchase thrifting products at Pasar Melati, Medan City, with an unknown or biased total population size. Therefore, the sampling technique used is the Lemeshow formula, which allows for sample size calculation when the total population is not known with certainty. The sampling method applied is accidental sampling, where respondents are randomly selected based on their availability and willingness to participate in the study, totaling 96 respondents. The results of the study indicate that price has a significant influence on consumer purchasing decisions for thrifting products at Pasar Melati, Medan City. Product quality also affects consumer purchasing decisions for thrifting items at the same location. Brand image contributes to consumers’ considerations in determining purchasing decisions for thrifting products at Pasar Melati. Simultaneously, price, product quality, and brand have a significant effect on consumer purchasing decisions for thrifting products at Pasar Melati, Medan City.